Removal of phenolic compounds in olive mill wastewater by silica-alginate-fungi biocomposites - Duarte, K. R.
This study aims to attempt a treatment strategy based on fungi immobilized on silica-alginate (biocomposites) for removal of phenolic compounds in olive oil mill wastewater (OMW), OMW supplemented (OMWS) with phenolic compounds and water supplemented (WS) with phenolic compounds, thus decreasing its potential impact in the receiving waters. Active (alive) or inactive (death by sterilization) Pleurotus sajor caju was encapsulated in alginate beads. Five beads containing active and inactive fungus were placed in a mold and filled with silica hydrogel (biocomposites). The biocomposites were added to batch reactors containing the OMW, OMWS and WS. The treatment of OMW, OMWS and WS by active and inactive biocomposites was performed throughout 28 days at 25 C. The efficiency of treatment was evaluated by measuring the removal of targeted organic compounds, chemical oxygen demand (COD) and relative absorbance ratio along the time. Active P. sajor caju biocomposites were able to remove 64.6–88.4 % of phenolic compounds from OMW and OMWS and 91.8–97.5 % in water. Furthermore, in the case of OMW there was also a removal of 30.0–38.1 % of fatty acids, 68.7 % of the sterol and 35 % of COD. The silica–alginate–fungi biocomposites showed a high removal of phenolic compounds from OMW and water. Furthermore, in the application of biocomposites to the treatment of OMW it was observed also a decrease on the concentration of fatty acids and sterols as well as a reduction on the COD.